Analysis of the Development of The Digital Economy in Our Country - Raufov Quvonchbek Khusin ugli (Scientific Trends, 2023)
In the 21st century, the digital economy is developing very rapidly. The use of information technologies to generate new ideas remains the demand of the century. In such conditions, many countries are developing new plans and decisions on the development of the digital economy. Prospective actions in these directions are also being carried out in Uzbekistan. This article examines the digital economy and the development of the digital economy in Uzbekistan.
Keywords: Digital economy, e-commerce, innovation , technology, services, system, strategy.